The Influence of Profitability, Liquidity, Solvency, and Company Size on the Timeliness of Financial Report Submission - Yuliana Fitri; Kholida Atiyatul Maula (LPPM STIE EKA PRASETYA, 2023)
Some companies that are late in submitting their financial reports on time will be subject to administrative sanctions and fines in accordance with the provisions established by the law, but with the imposition of these administrative sanctions and fines, it turns out that many companies are still late in submitting their annual financial reports. The purpose of this research is to determine, analyze, and describe four factors, namely profitability, liquidity, solvency, which may affect the timeliness of financial reporting in consumer goods industry sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2018-2020. The research method used is a quantitative approach with an applied method. The total sample obtained based on the sampling technique method is 45 companies. The analysis technique used in this research includes descriptive statistical analysis, multiple linear regression analysis, and hypothesis testing using the SPSS application. The results of the research show that (1) Profitability variable (ROA) does not have a partial effect on timeliness, (2) Liquidity variable (CR) used has a partial effect on timeliness, (3) Solvency variable (DAR) does not have a partial effect on timeliness, (4) Company size variable (SIZE) does not have a partial effect on timeliness, (5) Profitability (ROA), liquidity (CR), solvency (DAR), and company size (SIZE) simultaneously affect timeliness.